How to Use the Buttonhole Technique: A Single-Center Experience. Issue 2 (April 2017) - Novelli, Andrea; Amabili, Sofia; Cicconi, Beatrice; Mandolesi, Luca; Solano, Giuseppe; Oliva, Elena; Bruni, Francesco
Suitable vascular access is a prerequisite for adequate and efficient hemodialysis. Cannulation of an arteriovenous fistula (AVF) can be difficult in some patients, and this has led to the widespread use of the buttonhole (BH) technique. This paper describes our experience in BH technique practice and provides a pocket guide for clinicians and nurses who would like to approach it. Our experience shows that inadequate technique management is often associated with a higher vascular access infection rate. We used the BH technique in 25, 985 punctures, recording only 13 puncture site infections. Two AVFs were lost due to severe infection and symptomatic arterial hypotension. The inclusion criteria were widened in order to collect data from most of the hemodialysis population. Our results confirm the validity of the BH technique and will serve to make crucial clinical considerations as well as strategies to prevent BH technique-related complications.